Editorial: The researcher and the research in criminal sciences in contemporaneity - Caíque Ribeiro Galícia (Revista Brasileira de Direito Processual Penal)
This editorial presents a general analysis of the contemporary reality of the researcher and research in criminal sciences in Brazil. The researcher's profile is sought as an important component to understand the choices of criminal science research guidelines, with a focus on overcoming the false claim of impartiality of the subject-researcher. In this panorama, an analysis of legal research in Brazil is made, highlighting the most important role in the better understanding of legal science, but also as a factor of social, cultural, political and economic development.